A Critical Analysis of Vocabulary Acquisition in the Absence of Contextual Language Environments: Implications for Effective Pedagogy - Nurhidayah Nurhidayah; Riko Andrian; Widiya Yul (Universitas Muhammadiyah Gorontalo, 2025)
The objective of this research is to understand the factors that influence vocabulary acquisition, thereby enhancing students' linguistic skills within a language environment. The approach used in this study is phenomenology, employing an interpretive paradigm. The method utilized in this research is descriptive qualitative. The results of the study reveal that learning Arabic within a language environment plays a crucial role in vocabulary acquisition and constitutes a part of the learning strategy. In the absence of a language environment in Arabic learning, the following impacts on vocabulary acquisition are observed: 1) students are likely to forget the vocabulary they have memorized easily, and 2) their vocabulary repertoire will not expand without memorization. Thus, the presence of a language environment can eliminate the need for vocabulary memorization. A conducive language environment plays a crucial role in enhancing students' Arabic language proficiency, and thus should be integrated into language learning strategies. Alternative strategies, such as elaboration and the creation of a language-rich environment, are effective in optimizing vocabulary acquisition, particularly in less supportive settings.